2019
DOI: 10.1128/mbio.01083-19
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Colistin Resistance Mechanisms in Extensively Drug-Resistant Acinetobacter baumannii Clinical Isolates

Abstract: Nosocomial infections with Acinetobacter baumannii are a global problem in intensive care units with high mortality rates. Increasing resistance to first- and second-line antibiotics has forced the use of colistin as last-resort treatment, and increasing development of colistin resistance in A. baumannii has been reported. We evaluated the transcriptional regulator PmrA as potential drug target to restore colistin efficacy in A. baumannii. Deletion of pmrA restored colistin susceptibility in 10 of the 12 exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 32 publications
2
98
0
Order By: Relevance
“…Conversely, the mutation A226V in the histidine kinase A (phosphoacceptor) domain of PmrB was observed in all ColR isolates, and not in the ColS ones (Figure 1). This mutation has been described in several prior studies, associated with ColR strains (Arroyo et al, 2011;Mavroidi et al, 2015Mavroidi et al, , 2017Dortet et al, 2018;Trebosc et al, 2019).…”
Section: Colistin Resistance Mechanismssupporting
confidence: 53%
See 1 more Smart Citation
“…Conversely, the mutation A226V in the histidine kinase A (phosphoacceptor) domain of PmrB was observed in all ColR isolates, and not in the ColS ones (Figure 1). This mutation has been described in several prior studies, associated with ColR strains (Arroyo et al, 2011;Mavroidi et al, 2015Mavroidi et al, , 2017Dortet et al, 2018;Trebosc et al, 2019).…”
Section: Colistin Resistance Mechanismssupporting
confidence: 53%
“…Colistin resistance may also result from the overexpression of etpA, a pmrC homolog. This is mediated by insertional inactivation of a gene encoding an H-NS family transcriptional regulator (Lucas et al, 2018) or by integration of insertion sequence elements upstream of the eptA gene itself (Gerson et al, 2019;Potron et al, 2019;Trebosc et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Trebosc et al [52] showed the novel colistin resistance mechanism of A. baumannii mediated by genetic integration of the insertion element ISAbaI upstream of the PmrC homolog EptA (93% identity), leading to its overexpression. Besides, the detection of a duplicated ISAbaI-eptA cassette, suggesting that this colistin resistance determinant may be inserted in a mobile genetic element.…”
Section: A Baumanniimentioning
confidence: 99%
“…The presence of the insertion sequence ISAba11 in lpxC or lpxA also causes inactivation of LPS production (Moffatt et al, 2011). Alternatively, phosphoethanolamine transferase overexpression can result from the integration of the ISAbaI upstream of a pmrC homolog eptA leading to colistin resistance (Trebosc et al, 2019).…”
Section: Introductionmentioning
confidence: 99%